THE EFFECT OF VILLAGE BUDGET ACCOUNTABILITY AND TRANSPARENCY ON COMMUNITY EMPOWERMENT IN TANJUNG LANJUT VILLAGE MUARO JAMBI REGENCY - Saputra, Anju; Sam, Iskandar; Jumaili, Salman (Jurnal Cakrawala Akuntansi, 2026)
This study is motivated by the importance of accountability and transparency in village budget management to enhance community empowerment. This study aims to analyse the effect of accountability and transparency on community empowerment in Tanjung Lanjut Village, Sekernan District, Muaro Jambi Regency, Jambi Province. This research employed a quantitative approach using a survey method through questionnaires distributed to 64 respondents. The data were analysed using multiple linear regression with the assistance of SPSS version 29. Hypothesis testing was conducted using the t-test to examine partial effects and the F-test to examine simultaneous effects at a 5% significance level. The results show that accountability has a positive and significant effect on community empowerment, and transparency also has a positive and significant effect on community empowerment. Simultaneously, both variables significantly affect community empowerment. This study contributes to the literature by providing empirical evidence on the role of accountability and transparency as determinants of community empowerment at the village government level, a context that remains underexplored in prior research. Unlike studies conducted in urban or institutional settings, this study demonstrates that even in rural governance, sound financial management practices are critical drivers of public trust and active community participation. These findings offer practical guidance for village policymakers to prioritize transparent and accountable budget management as a strategic lever for sustainable community empowerment.